The Atlas of Bacterial & Archaeal Cell Structure: an Interactive Open-Access Microbiology Textbook - Catherine M. Oikonomou (American Society for Microbiology, 2021)
ABSTRACT Here, we describe a new open-access digital textbook for microbiology, The Atlas of Bacterial & Archaeal Cell Structure (available at cellstructureatlas.org). The book addresses a fundamental gap in existing textbooks, namely, what bacterial and archaeal cells look like and how the macromolecular structures they contain give rise to their diverse and complex functions. The interactive, multimedia resource features real data from more than 150 cells belonging to approximately 70 different species, imaged by cutting-edge cryogenic electron microscopy (cryo-EM). Complementary animations show the cellular machinery in action. Only a basic familiarity with fundamental biology concepts is required to understand the material, which targets a wide range of students in courses from general biology for nonmajors to specialized graduate-level microbiology. The content can be digested in several hours, making it well suited to be assigned as a supplemental resource for a course covering either more diverse topics in cell biology or a more specialized topic such as medical microbiology. By making this resource freely available online, we hope it will serve students in diverse educational settings, including self-directed learners.